Mirrors in Shakespeare and Early Modern English Drama - Finger, Valentina (Bloomsbury Publishing (UK), 2026)
Mirrors in the early modern playhouse function as figures of theatricality, reflecting gender dynamics and challenging sovereign power, in this open-access study of their use as stage props and rhetorical devices in plays by Shakespeare and his contemporaries. Combining approaches from literary studies and performance studies with extensive research into material history, Valentina Finger highlights the rich complexity of mirrors and acts of mirroring on the early modern stage. The case studies in this book traverse myths of monarchs and imperial mirrors in Richard II and Macbeth , explore acts of exemplary self-government and court politics in Edward I and Bussy D'Ambois , constitute cosmetic mirrors as canvases for feminine self-authorship in The Duchess of Malfi and The Devil's Charter and illuminate the interplay of scientific knowledge, magic and trick glasses in The Alchemist and A Game at Chess . Within this range of Shakespearean drama and lesser-studied plays by Shakespeare's contemporaries, each chapter examines political and literary history, material and visual culture, as well as gender and power dynamics. Focusing on the roles of mirrors as props and tropes in the early modern playhouse, this book contributes to our understanding of broader cultural, social and religious norms as they were debated in England around 1600. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com Open access was funded by the SFB 1369 Vigilanzkulturen (CRC 1369 Cultures of Vigilance) at Ludwig-Maximilians-Universität Munich with resources provided by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation).